Hubungan Antara Tingkat Stres dengan Kejadian Pityriasis Sicca pada Siswa Asrama SMA-IT Nur Hidayah Kartasura - Fa'izah, Chintya Nur, dr. Flora Ramona SP, M.Kes, SpKK, dr. Listiana Masyita Dewi (2016)
Backgrounds:Pityriasis sicca is a one of mild skin disorder of the scalp shown by smooth and rough scales caused by P.ovale. The incidence of PS increased in adolescents and young adults. PS caused by multifactorial mechanism, and one of them is stress. The level of stress is closely related to the high activity of sebaceous glands resulting in increased growth of P. ovale. Objective:The purpose of this study was to determine the relationship between stress levels with the incidence of pityriasis sicca in Nur Hidayah IT Kartasura High School Boarding students. Method: This research was observational analytic with cross sectional approach .The sample size was 50 samples by purposive sampling technique. Data were collected by recording the data from the primary data, L-MMPI and DASS questionnaire. Data analysis was performed with SPSS using contingency coefficient. Result: From 50 respondents PS is mostly found among respondents with moderate and severe stress level by 20%. From the contingency coefficient test r value was 0.394 and p value was 0.057. This mean that the value of r between 0.2-0.4, so it has a weak correlation, while the p value >0.05 indicates that the variable stress levels do not have any correlation with the incidence of the pityriasis sicca. Conclusion:There was nosignificant correlation between stress levels with the incidence of PS in Nur Hidayah IT Kartasura High School Boarding students.